Effect of Irradiation and Cholesterol and Progesterone on Cardiac Glycoside Production From Shoots of Digitalis lanata Plant In Vitro. - المختار, سراب عبد الهادي; حمد, محمد شهاب (Journal of Kerbala for Agricultural Sciences, 2015)
Seeds of foxglove (Digitalis Lanata) were irradiation with (0,30) gray of gamma ray and sown in sold MS media ,after one month shoot tips 2 cm were taken and cultured on MS media provide with 2 mg/l BA and either cholesterol or progesterone at 0,1,2,3mg/l of each, progesterone at 2mg/l gave the highest values of Lanatoside, Digoxin, Digitoxin and Gitoxin were(54.89, 67.62, 106.66 and 88.14) µg/g of dry weight respectively and highest content of chlorophyll and carbohydrates were 1.92 and 2.67mg/g respectively. Irradiation with 30 gray improved the characters test, it gave(66.15, 72.87, 128.67, 94.31) µg/g of the cardiac glycosides respectively.